1986
DOI: 10.1557/proc-83-143
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry of Thin Palladium Films

Abstract: The properties of Pd monolayers on several transition metal substrates are dramatically different from the surface properties of bulk Pd single crystals. The changes include a large rehybridization of the Pd atoms to a noble metal electronic configuration and a concomitant reduction in CO and H2 chemisorption bond strengths. We present here temperature programmed desorption (TPD) studies of CO, NO, H2, and C2H4 chemisorption on thin epitaxial Pd films on Nb(110). Our resuAs confirm for all of these gases a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The lack of sensitivity of reaction methanethiol is different from other studies of the chemistry of ultrathin metal films. For example, the electronic and chemical properties of Pd deposited on Nb(110), Mo(100), Ru(0001), and Re(0001), as well as Ni on Mo(110), were extremely sensitive to the admetal coverage and structure. The investigations of Pd thin films used molecules with π-bonds, such as ethylene and CO, as probes for chemical differences.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of sensitivity of reaction methanethiol is different from other studies of the chemistry of ultrathin metal films. For example, the electronic and chemical properties of Pd deposited on Nb(110), Mo(100), Ru(0001), and Re(0001), as well as Ni on Mo(110), were extremely sensitive to the admetal coverage and structure. The investigations of Pd thin films used molecules with π-bonds, such as ethylene and CO, as probes for chemical differences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of other metal overlayers deposited on metal substrates have shown that molecules like CO, H 2 , NO, and ethylene have desorption characteristics on the monolayer films that are different than on the bulk metals. 4,[6][7][8][9][10]68,69 It is interesting to note that the molecules for which a sensitivity to surface structure has been reported have π bonds. These results suggest that the degree of chemical sensitivity to the surface geometric structure depends strongly on the reactant bound to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported for CO adsorption on several other thin metal films supported on refractory metals. [4][5][6][7][8][9][10] Herein, we discuss the reactions of 2-propanol on Co-covered Mo(110). Cobalt overlayers on Mo(110) have been previously investigated in detail, and the lattice spacing was found to depend on Co coverage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations